A multimodal approach to reducing post‐caesarean opioid use: a quality improvement initiative. (1st February 2022) - Llarena, Natalia C.; Krivanek, Kevin; Yao, Meng; Kim, Daniel D.; Devarajan, Jagan; Ayad, Sabry; Chiang, Eric
Abstract: Objective: To evaluate the impact of a QI initiative to reduce post‐caesarean opioid use. Design: Retrospective cohort study. Setting: Academic hospital in the USA. Population: Women over 18 years undergoing caesarean section. Methods: A quality improvement (QI) initiative titled Reduced Option for Opioid Therapy (ROOT) was implemented in women undergoing caesarean section. The intervention included implementation of a postpartum order set maximising the use of scheduled NSAIDs and acetaminophen. Additionally, nursing education promoted non‐opioid therapy as first‐line, with opioids reserved for breakthrough pain. Performance feedback was provided to nursing staff on a bimonthly basis. Post‐caesarean opioid use was reviewed in the 6 months before and after implementation of ROOT. Main outcome measures: The primary outcome was the total morphine milligram equivalents (MME) consumed during the postpartum admission. Secondary outcomes included opioid use per postoperative day, the proportion of opioid‐free admissions, the percentage of patients discharged with a prescription for opioids, prescription size, and pain scores. Results: Following implementation of ROOT, median inpatient opioid use decreased by more than 60%, from 75 to 30 MME per admission ( P < 0.001). The proportion of opioid‐free admissions increased from 12.6% pre‐intervention to 30.7% post‐intervention ( P < 0.001). Additionally, the median opioid dose prescribed at discharge decreased in the post‐intervention cohort, and the proportion of patients discharged without an opioid prescription increased. The reduction in opioids was associated with a slight decrease in patient‐reported pain scores. Conclusions: Implementation of ROOT significantly reduced opioid use while achieving comparable pain control. Tweetable abstract: Nursing education, and use of an order set prioritising non‐opioid analgesics reduces post‐caesarean opioid use. Tweetable abstract: Nursing education, and use of an order set prioritising non‐opioid analgesics reduces post‐caesarean opioid use. This article includes Author Insights, a video abstract available at https://vimeo.com/bjogabstracts/authorinsights17094